Legal Aspects of Personal Data Protection in Cross-Border Data Flows within Bilateral Comprehensive Trade Agreements - Iqbal shaukat (The International Journal of Law Review and State Administration, 2026)
The rapid growth of the global digital economy has driven massive cross-border data flows, making data a highly valuable economic commodity. However, this phenomenon raises critical concerns regarding state sovereignty and the protection of personal data. This study examines the legal aspects of personal data protection within cross-border data flows under Bilateral Comprehensive Trade Agreements. Using a normative juridical research method with a statutory and comparative approach, this paper analyzes how bilateral trade agreements harmonize conflicting interests between trade liberalization and data privacy enforcement. The findings reveal that while comprehensive trade agreements increasingly include digital trade chapters to facilitate seamless data transmission, significant fragmentation remains due to differing national legal frameworks such as the stringent standards of the EU’s GDPR versus the more market-oriented approaches. This study concludes that to prevent regulatory loopholes and ensure legal certainty, future bilateral trade agreements must adopt robust adequacy decision mechanisms, mutual recognition principles, and clear dispute settlement clauses that treat data privacy not as a barrier to trade, but as a foundational element of digital trust.